Impactos do advento do Uber frente ao transporte coletivo urbano em São Carlos - Brentini, Guilherme Dias (2021)
Currently, with the advent of technology, lifestyle has been undergoing big changes. The way of moving in cities is no different. With the creation of car transport by apps, a new way of getting around in cities emerged. Such businesses way gain space every day for offering to their users a quality service that combines, above all, attractive prices and more safety. In addition, they offer a service that covers routes not served by public transport. This paper, through an online form, seeks to understand and map the target audience of Uber passengers in São Carlos-SP, to understand if this transportation mode is a substitute or a complement to urban public transport. It was noted that 70% of survey participants started using Uber instead of buses in the COVID-19 pandemic. The main reason is health, in this case replacing travel via public transport. The form was answered by a group that represents a small sample space when compared to the entire population of the city. So, it is suggested that futures works investigate more cases to improve the conclusions presented here. Furthermore, it is important to emphasize the interference of the period experienced during the pandemic in the results obtained. Since the search for more health-related safety, there is a certain migration of travel to Uber.